SUPERVISED STAGE: CONSTRUCTION OF KNOWLEDGE AND PRACTICES PHYSICAL EDUCATION IN EARLY CHILDHOOD EDUCATION. (Fiep Bulletin - online, 2012)
Analyzes ways of producing knowledge and practices in the disciplines of Supervised Physical Education in Early Childhood Education. The research is qualitative in nature and literature, focusing on analysis as a source of books, scientific journals in the area, loose and print publications. It is concluded that the relationship between stage establishes the academic and professional world, constituting the identity of the same. It is essential that, from this study, further investigations about the supervised training in Physical Education as part of his childhood and formative instruments are carried out, considering the possibilities of construction of knowledge and relevant teaching tool that can make the portfolio.
Keywords: Supervised Stage; Early Childhood Education; Portfolio.